Code switching patterns in Kazakh-Russian hybrid language practice: An empirical study - Valeria E. Chernyavskaya; Sholpan K. Zharkynbekova (Peoples' Friendship University of Russia (RUDN University), 2024)
The study investigates Kazakh-Russian and Russian-Kazakh code switching in the framework of hybrid language practice to provide insights into the sense-making process among bilinguals. The unique characteristics of the synchronic linguistic situation in Kazakhstan stem from historically rooted ethnic bi- and multilingualism. Language switching has evolved into a tool for addressing communicative partners and sustaining communication in bilingual culture, rather than being viewed as a deviant pattern. It appears to be a dynamic resource for ensuring mutual understanding and harmonised communication. The study aims to reveal the motivations behind individuals' language switching, how Kazakh and Russian speakers explain hybrid communication, and their sentiments towards it. Data from two surveys conducted in January-February of 2021 and January of 2024 are presented. Each survey involved 50 respondents with higher education, ranging in age from 21 to 40, who have resided in Kazakhstan for an extended period, with many being native-born residents. We argue that switching between the Kazakh and Russian languages serves as a communicative tool utilised by Kazakh and Russian speakers to signify their belonging to a specific sociocultural community. The study posits that hybrid language practice can be viewed from two underlying perspectives: from a 'deficit' perspective, signalling limited proficiency in Russian or/and Kazakh, and from a more complex sense-making communicative perspective, assisting interaction. As part of the sense-making process and in sustaining interaction with communication partners, code switching serves an instrumental function. Importantly, hybrid language practice is not portrayed as a sign of cultural decline. There is no strong correlation between the mixing of Russian and Kazakh and social, cultural, and educational barriers. Further implications for research are prompted by the rapidly changing situation. The development of the Kazakh language as a state language is becoming a major goal and central focus in this evolving context, which inevitably raises the issues of linguistic ideology. Distinguishing between ideologically neutral analysis and critical analysis of language use as a tool of symbolic power for specific social groups would provide a more gradient picture of the dynamics in Kazakhstan's bi- and multilingual situation.